Frequency recommendation for long term evolution network implementation using simple multi attribute rating technique - Angelia, Putri; Munadi, Rendy; Adriansyah, Nachwan Mufti (Institute of Advanced Engineering and Science, 2022)
The increasing demand for telecommunication services causes data traffic density. Therefore, in this research, the long-term evolution (LTE) network expansion was carried out using a choice of frequency bands of 700 MHz, 2100 MHz, and 2300 MHz. The analysis was carried out from the technical and economic aspects. Frequency band recommendations were obtained using the simple multi-attribute rating technique (SMART) method. This research was conducted using a case study of Semarang City. Based on the simulation results, the average of reference signal receive power (RSRP) values for frequency 700 MHz and 2300 MHz is in the very good range, while the frequency of 2100 MHz is in the good range. The signal to interference noise ratio (SINR) values for the three frequencies are in the normal category and the throughput values are in the very good category. The techno-economic calculations of the three frequencies, namely the value of internal rate of return (IRR), net present value (NPV), and payback period are included in the business category that is feasible to do. Based on the ranking results, the 700 MHz frequency is the most superior, both in terms of technical and economic aspects.